Integrasi Adab Pergaulan Islam dan Budaya Jawa dalam Pembelajaran PAI: Strategi Menghadapi Degradasi Moral Remaja di Era Digital - Fardani, Diah Novita; Zahra, Aryana (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2025)
"Integrating Islamic Social Etiquette and Javanese Culture in Islamic Religious Education Learning: A Strategy for Addressing Moral Degradation in Adolescents in the Digital Era"